Composite copper powder and preparation method and application thereof
By pickling and passivating the copper powder and complexing with Schiff alkali solution, an antioxidant layer is formed, which solves the problem of poor stability of conductive copper slurry in photovoltaic cells, significantly improving storage time and antioxidant properties , reduces the dummy and breaking of copper grid lines, improves conductive performance and low-temperature curing capabilities.
Patent Information
- Application Number
- CN202310736143.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
AI Technical Summary
The conductive copper paste used in photovoltaic cells has poor stability and short storage time at room temperature, which leads to problems such as false printing and gate breakage of copper grid lines.
The copper powder after pickling and passivation treatment is complexed with the solution containing Schiff base to form an antioxidant layer, reduce the distribution of Cu2+ on the surface, and avoid the catalytic effect of free Cu2+ on the resin and curing agent, thereby improving copper. Antioxidant properties and storage properties of powder.
It significantly improves the storage time and oxidation resistance of the conductive paste, reduces the dummy and gate breaking of the copper grid line, and improves the conductive performance and low-temperature curing ability.
Smart Images

Figure CN119159073A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of conductive materials, and in particular to a composite copper powder and a preparation method and application thereof. Background Art
[0002] Due to the increasing population base, the world's demand for energy is more urgent. As the engine of the national economy, energy has always attracted the attention of governments around the world. Solar energy is one of the most important renewable energy sources for mankind. As a pollution-free, renewable, and clean energy with huge reserves, it has a bright future. According to statistics, the solar energy power received on the earth is about 8×10 13 kW / s. If 0.1% of this energy is converted into electrical energy, and assuming that the conversion efficiency of solar energy into electrical energy is 10%, the total amount of electricity generated by the earth in a year is about 1×10 17 kWh, this total electricity generation is approximately 40 times the global energy consumption per year.
[0003] Photovoltaic power generation is a clean energy technology that uses semiconductor devices to directly convert solar cells into electrical energy. In the future use of energy, photovoltaic power generation will become the main energy form. At present, in order to reduce the cost of photovoltaic cells, attempts have been made to replace silver with other metals. Among the existing metals, copper is the closest to silver in conductivity, but copper itself is highly active and has a short storage time at room temperature in conductive copper paste. In addition, in the prior art, the copper powder used in the copper paste has a low tap density, and the copper grid line is prone to virtual printing and broken grids, so it has not yet been widely used in photovoltaic cells. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the conductive copper paste used in photovoltaic cells has poor stability and short storage time at room temperature.
[0005] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a composite copper powder, the method comprising:
[0006] S1, pickling the copper powder to obtain pickled copper powder
[0007] S2, passivating the pickled copper powder and performing a first washing and drying to obtain passivated copper powder;
[0008] S3, mixing the passivated copper powder with a solution containing a complexing agent to carry out a complexing reaction;
[0009] S4, centrifuging the material after the complex reaction and taking the precipitate for a second washing and drying;
[0010] Wherein, the passivation treatment comprises mixing the pickled copper powder with a solution containing saturated fatty acid and then heating the mixture; and the complexing agent is a Schiff base.
[0011] The preparation method of the composite copper powder provided by the present invention comprises adding a solution containing a Schiff base to the Cu distributed on the surface of the anti-oxidation layer. 2+ The copper ion complex is formed by complexation. After the complexation reaction, the material is washed, which greatly reduces the Cu distributed on the surface of the antioxidant layer. 2+ ; Avoids the free Cu in the rolling process when copper powder is used in conductive paste 2+ The catalytic effect on the resin and curing agent ensures the stability of the slurry and increases the storage time of the conductive slurry.
[0012] The second part of the present invention provides composite copper powder prepared by the above-mentioned preparation method.
[0013] The composite copper powder of the present invention has significantly improved antioxidant performance and storage performance, and has a high tap density. When used in conductive slurry, the volume of the copper powder of the same mass is significantly reduced, thereby reducing the viscosity of the conductive slurry and reducing the occurrence of virtual printing and broken grids of copper grid lines.
[0014] The third aspect of the present invention provides a conductive metal paste, which includes the aforementioned composite copper powder.
[0015] The conductive metal paste disclosed in the present invention has high square resistance, excellent conductive performance, good low temperature curing, good oxidation resistance, and significantly improved storage time. When the conductive paste of the present invention is used to make copper grid lines, the situation of false printing and broken grids is greatly reduced.
[0016] The fourth part of the present invention provides the application of the preceding conductive metal paste in photovoltaic cells.
[0017] Through the above technical scheme, the preparation method of the composite copper powder provided by the present invention can passivate the copper powder and form an antioxidant layer on the surface of the copper powder, thereby improving the antioxidant performance of the copper powder; using a solution containing Schiff base to passivate the Cu distributed on the surface of the antioxidant layer. 2+ The copper ion complex is formed by complexation. After the complexation reaction, the material is washed, which greatly reduces the Cu distributed on the surface of the antioxidant layer. 2+ The composite copper powder of the present invention has a high tap density. When used in conductive paste, the volume of the copper powder of the same mass is significantly reduced, thereby reducing the viscosity of the conductive paste and reducing the occurrence of virtual printing and broken gates of copper grid lines.
[0018] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0020] Figure 1 The electron microscope image of the conductive metal paste of the present invention is shown. DETAILED DESCRIPTION
[0021] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0022] A first aspect of the present invention provides a method for preparing a composite copper powder, the method comprising:
[0023] S1, pickling the copper powder to obtain pickled copper powder
[0024] S2, passivating the pickled copper powder and performing a first washing and drying to obtain passivated copper powder;
[0025] S3, mixing the passivated copper powder with a solution containing a complexing agent to carry out a complexing reaction;
[0026] S4, centrifuging the material after the complex reaction and taking the precipitate for a second washing and drying;
[0027] Wherein, the passivation treatment comprises mixing the pickled copper powder with a solution containing saturated fatty acid and then heating the mixture; and the complexing agent is a Schiff base.
[0028] The Schiff base in the present invention is well known to those skilled in the art, that is, a type of organic compound containing an imine or azomethine characteristic group (-RC=N-).
[0029] The preparation method of the composite copper powder provided by the present invention passivates the copper powder and forms an anti-oxidation layer on the surface of the copper powder, thereby improving the anti-oxidation performance of the copper powder; the Cu distributed on the surface of the anti-oxidation layer is passivated by adding a solution containing a Schiff base. 2+ The copper ion complex is formed by complexation. After the complexation reaction, the material is washed, which greatly reduces the Cu distributed on the surface of the antioxidant layer. 2+ ; Avoids the free Cu in the rolling process when copper powder is used in conductive paste 2+ The catalytic effect on the resin and curing agent ensures the stability of the slurry and increases the storage time of the conductive slurry.
[0030] According to the present invention, the Schiff base can be selected from at least one of salicylaldehyde Schiff base, thiol-containing Schiff base, aromatic Schiff base and carboxylic acid-containing Schiff base, preferably at least one of salicylaldehyde Schiff base and thiol-containing Schiff base; optionally, in the solution containing the complexing agent, the concentration of the complexing agent is 0.05 to 5 mol / L. 2+ Complexation reduces the amount of Cu distributed on the surface of the antioxidant layer 2+ quantity, avoiding free Cu 2+ The reaction of the alcohol amine accelerator commonly used in the copper slurry reduces the loss of the accelerator, thereby enhancing the curing effect of the resin and the curing agent; by washing and removing the copper ion complex generated by the complexation, the problem of increased slurry viscosity caused by the presence of too many copper ion complexes is avoided, thereby ensuring the dispersibility of the slurry.
[0031] In a preferred embodiment of the present invention, in step S1, the pickling treatment comprises: placing the copper powder in a pre-cleaning solution for a first ultrasonic treatment and a first mechanical stirring to obtain a first material; centrifuging and drying the first material and placing it in an acid solution for a second ultrasonic treatment and a second mechanical stirring; wherein the pre-cleaning solution is selected from at least one of ethanol, petroleum ether, tetrahydrofuran, toluene and ethyl acetate, dichloromethane, n-hexane, cyclohexane, acetone, nitrogen-nitrogen dimethylformamide, dimethyl sulfoxide, and nitrogen-methyl pyrrolidone; the acid solution is selected from at least one of sulfuric acid, hydrochloric acid, nitric acid, aminosulfonic acid, and acetic acid, and H + The concentration is 0.1 to 5 mol / L. The pickling treatment method disclosed in the present invention can significantly increase the tap density of the copper powder, thereby ensuring that the copper powder can be better dispersed in the conductive slurry.
[0032] Further preferably, the conditions of the first ultrasonic treatment include: a frequency of 20 to 90 KHZ, a temperature of 25 to 50°C, and a time of 5 to 120 min; the conditions of the first mechanical stirring include: a rotation speed of 100 to 5000 rpm, a temperature of 25 to 50°C, and a time of 5 to 120 min; the conditions of the second ultrasonic treatment include: a frequency of 40 to 90 KHZ, a temperature of 25 to 50°C, and a time of 5 to 120 min; the conditions of the second mechanical stirring include: a rotation speed of 300 to 1000 rpm, a temperature of 25 to 50°C, and a time of 5 to 120 min. In a preferred embodiment of the present disclosure, the centrifugal treatment can be performed using a centrifuge at a rotation speed of 6000 to 10000 rps for 30 s.
[0033] According to the present invention, in the solution containing saturated fatty acids, the saturated fatty acids can be selected from at least one of stearic acid, palmitic acid, lauric acid, palmitic acid, capric acid, and formic acid, and the solvent can be selected from at least one of petroleum ether, ethanol, ethylene glycol, water, nitrogen-nitrogen dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, nitrogen-methyl pyrrolidone, and ethyl acetate; preferably, in the solution containing saturated fatty acids, the concentration of the saturated fatty acids is 0.1 to 5 mol / L.
[0034] According to the present invention, in step S2, the conditions for the passivation treatment may include: a temperature of 20 to 100° C. and a time of 5 to 12000 min; in step S3, the conditions for the complexation reaction may include: a temperature of 20 to 100° C. and a time of 5 to 120 min.
[0035] According to the present invention, the washing liquid used in the first washing and drying treatment and the washing liquid used in the second washing and drying treatment are independently selected from at least one of ethanol, petroleum ether, dimethylformamide, dimethyl sulfoxide, water, tetrahydrofuran and n-hexane.
[0036] The copper powder particles used in the present invention may be flaky copper powder particles and / or spherical copper powder particles; optionally, the particle size D50 of the flaky copper powder particles is 1 to 10 μm, preferably 2 to 5 μm; the particle size D50 of the spherical copper powder particles is 0.02 to 0.8 μm, preferably 0.05 to 0.2 μm.
[0037] The third part of the present invention provides composite copper powder prepared by the above-mentioned preparation method.
[0038] The composite copper powder provided by the present invention has a core-shell structure, and the antioxidant performance of the copper powder particles is improved by coating the surface of the copper powder particles with an antioxidant layer. At the same time, the composite copper powder of the present invention has a high tap density, and when used in a conductive slurry, the volume of the copper powder of the same mass is significantly reduced, thereby reducing the viscosity of the conductive slurry and reducing the occurrence of virtual printing and broken grids of copper grid lines.
[0039] In the present disclosure, the composite copper powder includes copper powder particles and an antioxidant layer coated on the surface of the copper powder particles; the tap density of the composite copper powder can be 3.0-5.5 g / mL, preferably 4.0-5.0 g / mL; the loss on ignition can be 0.05-0.8%, preferably 0.1-0.4%.
[0040] According to the present disclosure, based on the total mass of the composite copper powder, the weight proportion of the copper powder particles is 99.2 to 99.95 wt %, preferably 99.6 to 99.9 wt %.
[0041] The fourth aspect of the present invention provides a conductive metal paste, which includes the aforementioned composite copper powder.
[0042] Figure 1 The electron microscope image of the conductive metal paste of the present invention is shown. The conductive metal paste disclosed in the present invention has high square resistance, excellent conductivity, good low temperature curing, good oxidation resistance, and significantly improved storage time. When the conductive paste of the present invention is used to make copper grid lines, the situation of false printing and broken grids is greatly reduced.
[0043] The viscosity of the conductive metal paste provided by the present invention at a temperature of 25° C. and a rotation speed of 100 rpm may be 100 to 500 Pa·s, preferably 150 to 250 Pa·s.
[0044] Optionally, based on the total weight of the conductive metal paste, the content of the composite copper powder is 70-95wt%.
[0045] The conductive metal paste of the present invention may further include optional resin, curing agent, dispersant, coupling agent, accelerator, solvent and the like.
[0046] The fifth part of the present invention provides the application of the preceding conductive metal paste in photovoltaic cells.
[0047] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.
[0048] Example 1
[0049] Take 50g of flaky copper powder with a particle size D50 of 1μm and add them to a 250ml beaker, add 100ml ethanol solution for ultrasonic cleaning, and after ultrasonic cleaning for 30min, centrifuge and pour out the supernatant, wash three times with 80ml ethanol, and centrifuge and dry for use. Pour the dried copper powder into 80ml 0.5mol dilute sulfuric acid, heat it to 65℃ in a water bath, stir it with a mechanical stirrer for 30min, wash it with clean water three times after the end, filter and dry it for use, and obtain the copper powder after copper pretreatment.
[0050] Stearic acid and ethylene glycol solution were mixed in a ratio of 1:1, and copper powder was poured into the solution. After stirring at 35°C for 16 hours, the copper powder was washed with ethanol three times and then dried. The dried copper powder was stirred with the prepared salicylaldehyde ethylenediamine Schiff base aqueous solution for 30 minutes, washed with clear ethanol three times and then centrifuged and dried to obtain copper powder coated with stearic acid. The changes in tap density and burning loss of copper powder before and after treatment are shown in Table 1.
[0051] Table 1
[0052]
[0053]
[0054] Example 2
[0055] Take 50g of spherical copper powder with a particle size D50 of 200nm and add them to a 250ml beaker, add 100ml ethanol solution for ultrasonic cleaning, and after ultrasonic cleaning for 30min, centrifuge and pour out the supernatant, wash it three times with 80ml ethanol, and centrifuge and dry it for use. Pour the dried copper powder into 80ml 2mol dilute sulfuric acid, heat it to 65℃ in a water bath, stir it with a mechanical stirrer for 30min, wash it with clean water three times after the end, and filter and dry it for use. The copper powder after copper pretreatment is obtained.
[0056] Mix palmitic acid and ethylene glycol solution in a ratio of 1:2, pour copper powder into the solution, stir at 45°C for 12 hours, wash with ethanol three times and dry. Stir the dried copper powder with the prepared salicylaldehyde ethylenediamine Schiff base aqueous solution for 30 minutes, wash with clear ethanol three times and centrifuge and dry to obtain copper powder coated with stearic acid. The changes in tap density and burning loss of copper powder before and after treatment are shown in Table 2.
[0057] Table 2
[0058] Save time Tap density Burning Original copper powder 1.8g / ml 1% After copper powder pretreatment 3.0g / ml 0.1% After palmitic acid coating 4.5g / ml 0.45%
[0059] Example 3
[0060] Take 50g of spherical copper powder with a particle size D50 of 200nm and add them to a 250ml beaker, add 100ml ethanol solution for ultrasonic cleaning, and after ultrasonic cleaning for 30min, centrifuge and pour out the supernatant, wash it three times with 80ml ethanol, and centrifuge and dry it for use. Pour the dried copper powder into 80ml 2mol dilute sulfuric acid, heat it to 65℃ in a water bath, stir it with a mechanical stirrer for 30min, wash it with clean water three times after the end, and filter and dry it for use. The copper powder after copper pretreatment is obtained.
[0061] Mix palmitic acid and ethylene glycol solution in a ratio of 1:2, pour copper powder into the solution, stir at 45°C for 12 hours, wash with ethanol three times and dry. Stir the dried copper powder with the prepared 2-amino-5-mercapto-1,3,4-thiadiazole Schiff base aqueous solution for 30 minutes, wash with clear ethanol three times and centrifuge and dry to obtain copper powder coated with stearic acid. The changes in tap density and burning loss of copper powder before and after treatment are shown in Table 3.
[0062] Table 3
[0063] Save time Tap density Burning Original copper powder 1.8g / ml 1.0% After copper powder pretreatment 3.0g / ml 0.1% After palmitic acid coating 4.42g / ml 0.45%
[0064] Example 4
[0065] Take 50g of spherical copper powder with a particle size D50 of 200nm and add them to a 250ml beaker, wash them three times with 80ml ethanol, centrifuge and dry them for later use. Pour the dried copper powder into 80ml 0.5mol dilute sulfuric acid, heat it to 65℃ in a water bath, stir it with a mechanical stirrer for 30min, and then wash it with clean water for 3 times to obtain the copper powder after pretreatment. Filter and dry it for later use.
[0066] Stearic acid and ethylene glycol solution were mixed in a ratio of 1:1, and copper powder was poured into the solution. After stirring at 35°C for 16 hours, the copper powder was washed with ethanol three times and then dried. The dried copper powder was stirred with the prepared salicylaldehyde ethylenediamine Schiff base aqueous solution for 30 minutes, washed with clear ethanol three times and then centrifuged and dried to obtain copper powder coated with stearic acid. The changes in tap density and burning loss of copper powder before and after treatment are shown in Table 4.
[0067] Table 4
[0068] Save time Tap density Burning Original copper powder 1.8g / ml 1% After copper powder pretreatment 2.3g / ml 0.2% After palmitic acid coating 4.0g / ml 0.35%
[0069] Comparative Example 1
[0070] Take 50g of flaky copper powder with a particle size D50 of 1μm and add it to a 250ml beaker, wash it three times with 80ml of ethanol, and centrifuge and dry it for later use. Pour the dried copper powder into 80ml of 0.5mol dilute sulfuric acid, heat it to 65℃ in a water bath, stir it with a mechanical stirrer for 30min, and then wash it with clean water three times to obtain the copper powder after copper powder pretreatment. Filter and dry it for later use.
[0071] Stearic acid and ethylene glycol solution were mixed in a ratio of 1:1, and copper powder was poured into the solution. After stirring at 35°C for 16 hours, the mixture was washed with ethanol three times and dried to obtain copper powder coated with stearic acid. The changes in tap density and burning loss of copper powder before and after treatment are shown in Table 5.
[0072] Table 5
[0073] Save time Tap density Burning Original copper powder 3.8g / ml 0.5% After copper powder pretreatment 4.4g / ml 0.1% After palmitic acid coating 4.6g / ml 0.15%
[0074] Test Example 1
[0075] The copper powder, resin, curing agent, blocked isocyanate BI7960, coupling agent KH570, and accelerator prepared in Examples 1 to 4 and Comparative Example 1 were mixed in a mass ratio of 90:7:2:0.3:0.5:0.5 and dispersed and mixed evenly using a three-roll grinder. A vacuum planetary deaerator was then used for secondary dispersion and air in the slurry was removed to obtain a conductive copper slurry with a viscosity of 120 Pa·s (25°C). The slurry was stored at room temperature for 21 days, and the viscosity tracking was shown in Table 6.
[0076] Table 6
[0077] Save time 1 day (Pa·s) 3 days (Pa·s) 7 days (Pa·s) 21 days (Pa·s) Example 1 103 104 103 108 Example 2 120 121 123 121 Example 3 115 113 116 116 Example 4 118 115 120 119 Comparative Example 1 95 98 105 110
[0078] It can be seen from Table 6 that the conductive copper slurry prepared using the copper powder prepared in Examples 1 to 4 has good stability, and the viscosity is less affected by the storage time; the viscosity of the conductive copper slurry prepared using the copper powder prepared in Comparative Example 1 gradually increases with the extension of the storage time, and the stability is poor.
[0079] Test Example 2
[0080] The conductive copper paste of Test Example 1 was cured in a nitrogen atmosphere oven, and then the film thickness and sheet resistance of the cured film were tested, and the test results are shown in Table 2. The conductive copper paste cured sample was placed at room temperature (environment temperature 25±2°C, humidity 45±5%) for 21 days, and then its sheet resistance was measured, and the test results are shown in Table 7.
[0081] Table 7
[0082] Save time 1 day (mΩ / □) 3 days (mΩ / □) 7 days (mΩ / □) 21 days (mΩ / □) Example 1 10.8 10.7 11.3 10.9 Example 2 11 12.3 11.6 11.4 Example 3 12 12.5 12.3 12.7 Example 4 10.5 11 10.8 11.1 Comparative Example 1 11 11.2 12.3 14
[0083] It can be seen from Table 7 that the conductive copper paste prepared using the copper powder prepared in Examples 1 to 4 has good stability, and the sheet resistance is less affected by the storage time; the sheet resistance of the conductive copper paste prepared using the copper powder prepared in Comparative Example 1 gradually increases with the extension of the storage time, and the stability is poor.
[0084] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0085] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0086] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a composite copper powder, characterized in that: The method includes: S1, pickling the copper powder to obtain pickled copper powder S2, passivating the pickled copper powder and performing a first washing and drying to obtain passivated copper powder; S3, mixing the passivated copper powder with a solution containing a complexing agent to carry out a complexing reaction; S4, centrifuging the material after the complex reaction and taking the precipitate for a second washing and drying; Wherein, the passivation treatment comprises mixing the pickled copper powder with a solution containing saturated fatty acid and then heating the mixture; and the complexing agent is a Schiff base.
2. The preparation method according to claim 1, characterized in that: The Schiff base is selected from at least one of salicylaldehyde Schiff base, thiol-containing Schiff base, aromatic Schiff base and carboxyl Schiff base, preferably salicylaldehyde Schiff base and / or thiol-containing Schiff base; Optionally, in the solution containing the complexing agent, the concentration of the complexing agent is 0.05 to 5 mol / L.
3. The preparation method according to claim 1, characterized in that: In step S1, the pickling treatment includes: placing the copper powder in a pre-cleaning solution for a first ultrasonic treatment and a first mechanical stirring to obtain a first material; centrifugally drying the first material and placing it in an acid solution for a second ultrasonic treatment and a second mechanical stirring; The pre-cleaning solution is selected from at least one of ethanol, petroleum ether, tetrahydrofuran, toluene, ethyl acetate, dichloromethane, n-hexane, cyclohexane, acetone, nitrogen-nitrogen dimethylformamide, dimethyl sulfoxide and nitrogen-methyl pyrrolidone; the acid solution is selected from at least one of sulfuric acid, hydrochloric acid, nitric acid, aminosulfonic acid and acetic acid, and the acid solution contains H + The concentration is 0.1~5mol / L.
4. The preparation method according to claim 1, characterized in that: The conditions for the first ultrasonic treatment include: temperature of 25-50°C, time of 5-120 min; the conditions for the first mechanical stirring include: temperature of 25-50°C, time of 5-120 min; the conditions for the second ultrasonic treatment include: temperature of 25-50°C, time of 5-120 min; the conditions for the second mechanical stirring include: temperature of 25-50°C, time of 5-120 min.
5. The preparation method according to claim 1, characterized in that: In the solution containing saturated fatty acids, the saturated fatty acids are selected from at least one of stearic acid, palmitic acid, lauric acid, palmitic acid, capric acid, and formic acid, and the solvent is selected from at least one of petroleum ether, ethanol, ethylene glycol, water, nitrogen-nitrogen dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, nitrogen-methyl pyrrolidone, and ethyl acetate; preferably, in the solution containing saturated fatty acids, the concentration of the saturated fatty acids is 0.1 to 5 mol / L.
6. The preparation method according to claim 1, characterized in that: In step S2, the conditions for the passivation treatment include: a temperature of 20 to 100°C and a time of 1 to 12000 min; in step S3, the conditions for the complexation reaction include: a temperature of 20 to 100°C and a time of 1 to 120 min.
7. The preparation method according to claim 1, characterized in that: The washing liquid used in the first washing and drying treatment and the washing liquid used in the second washing and drying treatment are each independently selected from at least one of ethanol, petroleum ether, dimethylformamide, dimethyl sulfoxide, water, tetrahydrofuran and n-hexane.
8. The preparation method according to claim 1, characterized in that: The copper powder particles are flaky copper powder particles and / or spherical copper powder particles; Optionally, the particle size D50 of the flaky copper powder particles is 1 to 10 μm, preferably 2 to 5 μm; the particle size D50 of the spherical copper powder particles is 0.02 to 0.8 μm, preferably 0.05 to 0.2 μm.
9. Composite copper powder prepared by the preparation method according to any one of claims 1 to 8.
10. The composite copper powder according to claim 9, characterized in that: The composite copper powder comprises copper powder particles and an anti-oxidation layer coated on the surface of the copper powder particles; the tap density of the composite copper powder is 3.0 to 5.5 g / mL, preferably 4.0 to 5.0 g / mL; the ignition loss is 0.05 to 0.8%, preferably 0.1 to 0.4%.
11. The composite copper powder according to claim 9 or 10, characterized in that: Based on the total mass of the composite copper powder, the weight proportion of the copper powder particles is 99.20-99.95wt%, preferably 99.6-99.9wt%.
12. A conductive metal paste, characterized in that: The conductive metal paste comprises the composite copper powder according to any one of claims 9 to 11.
13. The conductive metal paste according to claim 12, characterized in that: The viscosity of the conductive metal paste at a temperature of 25° C. and a rotation speed of 100 rpm is 100 to 500 Pa·s, preferably 150 to 250 Pa·s.
14. The conductive metal paste according to claim 12, characterized in that: Based on the total weight of the conductive metal paste, the content of the composite copper powder is 70-95wt%.
15. Use of the conductive metal paste according to any one of claims 12 to 14 in photovoltaic cells.
Citation Information
Cited By
Copper powder and preparation method thereof, conductive copper slurry and application
CN120460719A
